Pelanggaran Elektoral Dan Erosi Demokrasi: Peran Money Politic Dalam Menghancurkan Nilai-Nilai Demokrasi - Rizqillah, Rizqillah; Daryono, Daryono; Aziz, Adi Nur (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The phenomenon of electoral violations increasingly widespread in Indonesia’s political contestation reflects the erosion of democratic values that should uphold the principles of participation, fairness, and accountability. One of the most prominent forms of electoral violations is money politics, where the distribution of material or financial benefits is used as an instrument to influence voters’ political choices. This article seeks to explore in depth how money politics contributes to the decline in democratic quality through a qualitative approach using a literature study method. The study was conducted by reviewing various academic sources, reports from independent institutions, and related regulations, which indicate that money politics not only undermines public trust in the democratic process but also perpetuates a transactional political culture that reduces citizens’ role to passive recipients of rewards. The main findings show that money politics has systemic implications for the weakening of democracy, including strengthening the dominance of political elites with large financial capital, creating electoral injustice, and neglecting leadership quality based on integrity and competence. This article concludes that to restore substantive democracy, comprehensive reforms are needed in the electoral regulatory system, improvement of political literacy, and strict law enforcement against electoral violations. Thus, this study affirms that money politics is not merely a procedural violation, but a fundamental threat to the values, ethics, and legitimacy of democracy itself.